The counterterrorism handbook : tactics, procedures, and techniques - Bolz, Frank, 1930-; Dudonis, Kenneth J.; Schulz, David P. (Boca Raton, FL : Taylor & Francis, 2005)
This book is an invaluable resource for those who recognize that preparation is the best defense in the war on terror. Revised and expanded to reflect information obtained since the September 11th attacks, this latest edition provides an understanding of the strategies, tactics, and techniques required to counter terrorism as it exists today. It illustrates essential topics such as the elements common to all terrorism, bomb threats, risk assessment, hostage situations, and weapons of mass destruction. New addition to the third edition include: provides a closer look at what transpired during and after the attacks on the World Trade Center and the Pentagon; discusses the current state of WMD's, including threats from chemical and biological agents and those posed by nuclear weapons; divulges the latest modes of domestic terrorism, including cyber-terrorism and eco-terrorism; discloses the latest information on what's going on with Homeland Security; covers recent INS laws as they relate to terrorist activity and how they effect homeland security.
Includes bibliographical references and index
Online version also available
Keywords: Terrorism -- Prevention